A COMPARATIVE STUDY REGARDING PAIN PERCEPTION AMONG MALES AND FEMALES OF UNIVERSITY STUDENTS IN PUNJAB, SINDH & BALOCHISTAN - Saiyida Tasmeera (Army Medical College Rawalpindi, 2021)
Objective: To compare gender differences on pain perception in Pakistani culture.